Size Is the Major Determinant of Pumping Rates in Marine Sponges - Morganti, Teresa Maria; Ribes, Marta; Yahel, Gitai; Coma, Rafel (Frontiers in Physiology, 2019)
1. Sponges play an important ecological function in many benthic habitats. They filter large volumes of water, retain suspended particles with high efficiency and process dissolved compounds. Nevertheless, the factors that regulate sponge pumping rate and its relation to environmental factors have been rarely studied. 2. We examined, in situ, the variation of pumping rates for five Mediterranean sponge species and its relationship to temperature, particulate food abundance and sponge size over two annual cycles. 3. Surprisingly, temperature and food concentration had only a small effect on pumping rates and the seasonal variation of pumping rates was small (1.9-2.5 folds). 4. Sponge size was the main determinant of the specific pumping rate (pumping normalized to a sponge volume or mass). Within the natural size distribution of each species the volume-specific pumping rate (PRV, mL min 1 (cm sponge)-3) decreased (up to 33 folds) with the increase in sponge volume (V, cm3), conforming to an allometric power function (PRV=aVb) with negative exponents. 5. The strong dependence of the size-specific pumping rate on the sponge size suggests that the simplistic use of this value to categorize sponge species and predict their activity may be misleading. For example, for small specimens, size-specific pumping rates of the two LMA species (allometric exponents b of -0.2 and -0.3) were similar to those of two of the HMA species (b of -0.5 and -0.7). However, for larger specimens, size-specific pumping rates were markedly different. 6. Our results suggest that the pumping rate of the sponges we studied can be approximated using the measured allometric constants alone in conjunction with surveys of sponge abundance and size distribution. This information is essential for the quantification of in situ feeding and respiration rates, and for estimates of the magnitude of sponge-mediated energy and nutrient fluxes at the community level. 7. Further work is required to establish if and to what extent the low seasonal effect and the strong size dependency of pumping rate can be generalized to other sponges and habitats.